A Large Case Series of Acute Pediatric Methotrexate Ingestions: Significant Clinical Effects Are Rare. Issue 10 (October 2016) - Hensley, Matthew D.; Bebarta, Vikhyat S.; Borys, Douglas J.
Abstract : Objective: Significant adverse effects after acute pediatric methotrexate (MTX) exposures have been limited to parenteral exposures. Treatment recommendations for pediatric MTX exposures do not differentiate between routes of exposure. We report the incidence of significant clinical effects and drug-specific treatments reported in a large series of acute, pediatric MTX ingestions. Methods: Poison center records of all MTX ingestions by patients younger than 17 years during 2000 to 2005 were collected from 6 poison centers. The cases included all MTX ingestions including those with additional substances. One trained reviewer, blinded to the study purpose, used a standardized data collection form to extract study data. Missing or conflicting data were reconciled with predetermined process. Results: Forty-seven cases were documented for 6 years, 42 (89%) of which were unintentional. Thirty-six percent (17/47) were male. The mean age for the unintentional ingestions was 3.7 years (range, 20 days–17 y; median, 2 y). Five cases (11%) were intentional suicidal ingestions in teenagers. The mean dose in acute, unintentional ingestions (AUIs) in all children and in children younger than 6 years was the same, 8 mg (range, 2.5–17.5 mg). Eleven patients (23%) had follow-up greater than 12 hours. No patient with an AUI developed MTX-induced sedation, hepatotoxicity, renal insufficiency, seizures, or bone marrow suppression. Three patients with an AUI received folinic acid, but no patients in this group received sodium bicarbonate or hemodialysis. One patient with an intentional suicidal exposure developed hepatotoxicity, but the patient also ingested a toxic dose of acetaminophen and valproate. Hemodialysis was performed once on this patient. No patient died. Conclusions: Acute pediatric MTX ingestion is uncommon. Methotrexate-induced seizure, renal failure, hepatic injury, and sedation were not documented in our series. Supportive care and observation only should be considered the mainstay of treatment of pediatric AUIs. Prospective verification of our findings is warranted.